Analisis Pengaruh Pacaran di Kampus dengan Tingkat IPK Mahasiswa - Akbar, Dutha Hajrul; Purnamasari, Putri; Said, Anggi Sundari Tubagus; Siswanto, Andika Prayoga; Pratama, Wahyu Ridho; Syahputra, M Irfan (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study aims to analyze the influence of romantic relationships among university students on their Grade Point Average (GPA). Romantic relationships are a common social phenomenon during emerging adulthood and may affect cs3tudents’ academic engagement, motivation, and psychological well-being. This research employed a quantitative correlational approach involving undergraduate students from a public university. Data were collected through questionnaires measuring relationship status, perceived partner support, academic motivation, and cumulative GPA. The results indicate that romantic relationship status alone does not have a significant direct effect on GPA. However, the quality of partner support shows a positive correlation with academic motivation, which indirectly influences GPA. These findings suggest that romantic relationships do not necessarily hinder academic achievement, but their impact depends on the quality of support and students’ ability to balance academic and personal life. This study contributes to the limited literature on romantic relationships and academic performance among university students in developing countries.